Herbicide resistant Phalaris minor A challenge for sustainable wheat production - Soni, Jeetendra Kumar; Nibhoria, Amarjeet; Punia, S S; Hota, Surabhi (Indian Farming, 2021)
Phalaris minor Retz. (little seed canary grass) is a rabi weed that mimics wheat crop and if left unattended, may lead to 15-40% or more yield loss. It predominates in the rice-wheat cropping system in Haryana, Punjab, Western Uttar Pradesh and states of the north-western Indo-Gangetic plains of India. Being morphologically similar to wheat, it often escapes from manual and mechanical control. Thus to control this weed, application of herbicide is the most appropriate tool. However, use of same herbicide repeatedly develops selection pressure resulting resistant weed population. Herbicide resistance started from the use of isoproturon to clodinafop, fenoxaprop, sulfosulfuron. Also, some of the biotypes developed resistance to some new herbicide viz., pinoxaden, mesosulfuron+iodosulfuron. As of now, multiple herbicide resistance has evolved in Phalaris minor, due to which sustainability of the wheat remains doubtful. To tilt the selection pressure in favour of resistant biotypes and to sustain wheat production, the use of new herbicides and its compatible mixtures having multifaced modes of action and herbicide rotation from year to year is necessary. To improve crop safety, the practice of optimized rate of the herbicide in combination with appropriate doses of other herbicides need to be followed, which will also broaden the spectrum of weed control and delay the evolution of resistance in weed species.